2013
DOI: 10.1142/s2010194513009951
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Various Functional Properties of Titania Thin Film Developed on Glazed Ceramic Wall Tiles

Abstract: A sol-gel based TiO 2 thin film was applied on glazed wall tiles for studying its various functional properties. Thin film was deposited by spin coating on the substrate and subjected to curing at different temperatures such as 600°C, 650, 700°C, 750°C and 800°C with 10 minutes soaking. The gel powder was characterized by FTIR, DTA/TG and XRD. Microstructure of thin film was analyzed by FESEM and EDX. Surface properties of the coatings such as gloss, colour difference, stain resistance, mineral hardness and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The decrease in hardness of coated substrate cured at 600 o C could be attributed to factors such as poor density of the film as evident from FESEM results, lower rutile phase formation and lack of proper adhesion of film due to non-softening of the glaze. Our earlier studies 13 showed that pure TiO 2 film had poor adhesion at 600 o C and it showed a jump from 2 to 5 Mohs only with increase in curing temperature from 600 o to 800 o C. This further supports the fact that the enhancement in hardness from 3 to 6 Mohs of TiO 2 -Fe 2 O 3 thin film coated sample is due to combined effect of factors such as softening temperature, fluxing action of iron oxides, highly dense and crystalline thin film with rutile as major phase and iron based oxides as minor phase. Downloaded by [Monash University Library] at 07:47 26 November 2014…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The decrease in hardness of coated substrate cured at 600 o C could be attributed to factors such as poor density of the film as evident from FESEM results, lower rutile phase formation and lack of proper adhesion of film due to non-softening of the glaze. Our earlier studies 13 showed that pure TiO 2 film had poor adhesion at 600 o C and it showed a jump from 2 to 5 Mohs only with increase in curing temperature from 600 o to 800 o C. This further supports the fact that the enhancement in hardness from 3 to 6 Mohs of TiO 2 -Fe 2 O 3 thin film coated sample is due to combined effect of factors such as softening temperature, fluxing action of iron oxides, highly dense and crystalline thin film with rutile as major phase and iron based oxides as minor phase. Downloaded by [Monash University Library] at 07:47 26 November 2014…”
Section: Discussionmentioning
confidence: 96%
“…[11][12][13] However, scanty literature is available with regard to the effect of these coatings on glazed ceramic surface properties such as gloss, stain resistance, hardness, etc; 6, 13, 14 these properties are also equally important in addition to the functional properties reported earlier. 11,12 In our previous work, 13 the effects of sol-gel based TiO 2 thin film on various surface properties of glazed wall tile such as gloss, colour difference, antibacterial property and chemical resistance were reported which indicated that TiO 2 thin film did not adhere on the surface after curing at 600 o -650 o C and exhibited adherence only in the curing temperature range of 700 o -800 o C even though tile exhibited superior functional properties compared to uncoated substrate. In order to increase its adhesion and to improve functional properties, Fe 2 O 3 was opted to incorporate into the TiO 2 system due to its various properties such as high refractive index, fluxing property, anti-bacterial property and colour imparting property.…”
Section: Introductionmentioning
confidence: 99%